Conjunctival botryomycoma: A case report - Khamaily, Mehdi; Salem, Joumany Brahim; Tarib, Imane; Bouchaar, Sidi Dahi Mounia; Zerrouk, Rachid; Mouzari, Yassine; El Asri, Fouad; Reda, Karim; Oubaaz, Abdelbarre (Global Journal of Medical and Clinical Case Reports, 2020)
The fleshy telangiectatic bud or pyogenic granuloma is a tumor-like lesion that develops from chronic inflammatory situations of the conjunctiva or the eyelid. The chalazion represents one of the most frequent of these situations. We report the case of a child who presented, after a chalazion, a pyogenic granuloma, treated by surgical removal.